THE PHILOSOPHY OF MIND MANAGEMENT AND THE MODERN CONCEPT OF ENSURING THE STABILITY OF HUMAN THINKING IN THE CONTEXT OF GLOBALIZATION (Scientific journal of the Fergana State University, 2026)
This study provides a philosophical and socio-gnoseological analysis of mind management and the modern concept of ensuring the stability of human thinking in the context of globalization. It examines how human consciousness is transformed under the influence of information flows, digital technologies, media manipulation, and global communication networks. The research identifies theoretical and methodological mechanisms that help preserve independent and critical thinking.